Legal Certainty in Determining The Amount of Duty Tax on Acquisition of Land and Building Rights (Bphtb) - Yanuaria, Tri; Polontoh, Herry M. (Faculty of Law, Universitas Pekalongan, 2024)
The research carried out in Jayapura City with the title